UCLA Encyclopedia of Egyptology: UEE (2008)
[Dt.:] Dieses noch im Aufbau befindliche Online-Lexikon versteht sich als Nachfolger des siebenbändigen Standardwerkes "Lexikons der Ägyptologie" (LÄ, hrsg. von Wolfgang Helck, Eberhard Otto und Wolfhart Westendorf). - [Engl.:] This online-encyclopedia is still in progress but it is supposed to substitute the standard reference work "Lexikon der Ägyptologie" (LÄ, edited by Wolfgang Helck, Eberhard Otto, and Wolfhart Westendorf).